The Effect of Co-authorship Network Density on the Performance of Postgraduate Programs - Jandir Pauli; Kenny Basso; Ravena Lopes Gobi; Alissa Bilhar (BBR: Brazilian Business Review)
By focusing on the performance of research teams in the management area, this study analyzes the effect of the co-authorship of scientific publications on the performance of postgraduate programs (PPGs) in management. The data was collected from management researchers in Brazil. Along with this, scientific publications from 2013 to 2016 were collected to comprise the social network of each PPG. The evaluation of the PPG was used as the dependent variable. The effects of the density of the co-authorship networks on the programs’ performance was verified. The results show that the density of the links between researchers follows a curvilinear trend of effect on organizational performance; that is, both highly dense and highly dispersed networks positively influence team performance. This study contributes to the literature on networks and team performance by providing evidence that the density of a network is not linearly related to performance.